Family anxiety in families with cancer patient - Kryvonis Тамара (Psychosomatic Medicine and General Practice, 2019)
Background. Cancer is a hard challenge for the patient’s family that causes changes in family functioning. In the study analyzed manifestations of family anxiety in families with cancer patients, depending on the stage of the disease and the level of adaptation in families. Contingent and research methods. Based on informed consent, a psychological examination of 288 families with a cancer patient was conducted, of which 174 patients were women and 114 were men. The respondents were further divided into subgroups depending on the stage of cancer and the level of adaptability of the family system. In the study used the Family Anxiety Questionnaire and the Family Adaptation and Cohesion Scale (FACES-3), a clinical-psychological interview. Results. Oncology was a powerful stress factor that affected family functioning and potentiated changes in marital relationships, perceptions of family events, attitudes and responsibilities. On the level of family, anxiety influenced the progression of cancer, the adaptability of the family system, the gender of the couple. With continued cancer or relapse, the family responds with increasing family anxiety, guilt and hyper responsibility for the family situation, tension. The progression of cancer in a family member led to increasing manifestations of family anxiety, which expressed in a sense of helplessness, uncontrollability, independence of the situation in the family from their efforts, exaggeration of responsibility for events, failure to fulfil family obligations. Particularly striking was the increased anxiety and guilt in patients’ wives. Violations of family adaptability were accompanied by increased family anxiety in all its structural components. Conclusions. Medical-psychological help for a family of cancer patients is an important part of interventions in oncology practice.